Efektivitas Pengelolaan Zakat Melalui Dana Alokasi Khusus dalam APBN - A. Muhyiddin Khotib (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
Many thinkers and Muslim scholars who continuously strive to make zakat as the main alternative in overcoming social inequality in the economic field. This effort starts from the reformulation of thought to its application stage. Prof. Dr. Yusuf al-Qardhawi (born 1926) who has gassed the concept of zakat through his two books Fiqh al-Zakat and Musykilatu al-Faqri wa kaifa ‘alajaha al-Islam. His two works are concrete proof that zakat has a strategic position in overcoming poverty. In my opinion, one of the problems which has not completed at the concept level is that the position of zakat is equated with prayer, fasting, and pilgrimage as fiqh of worship. This results in positioning zakat on privacy matters so that the state feels limited in intervening in the management of zakat because it feels uneasy and there is fear of criticism of people who do not want the state to take care of one's privacy when practicing their worship. The reasons that motivated the writer to study zakat in a dissertation entitled "Reconstruction of Zakat on Prayer to Mu'amalah in the perspective of Maqashid al-Shari'ah. The conclusion is that zakat is mu'amalah jurisprudence which has the dimension of worship and it doesn’t have a social dimension.